Comparative efficacy of different Chinese patent medicines in preventing restenosis after percutaneous coronary intervention: a systematic review and Bayesian network meta-analysis of randomized clinical trials - Fan, Jiasai; Li, Tianli; Pu, Fenglan; Guo, Nan; Wang, Jing; Gao, Yuqian; Zhao, Hongbing; Wang, Xian; Zhu, Haiyan (Frontiers in Pharmacology, 2024)
Background: Chinese patent medicines (CPMs) have curative effectiveness in preventing coronary restenosis. However, the relative efficacy between different CPMs has not been sufficiently investigated.Methods: Randomized clinical trials were searched from electronic databases including PubMed, Web of Science, Cochrane Library, Embase, CNKI, VIP, WanFang, SinoMed, Chinese Clinical Trial Registry and ClinicalTrials.gov. Bayesian network meta-analysis was performed to analyze CPMs' efficacy in preventing angiographic restenosis, recurrence angina, acute myocardial infarction, and target lesion revascularization after percutaneous coronary intervention. This is a provisional file, not the final typeset article Results: This network meta-analysis included 47 trials with 5077 patients evaluating 11 interventions. Regarding angiographic restenosis, the efficacy of CPMs (except Xuezhikang capsule) combined with standard treatment (Std) was superior to Std alone, and Guanxin Shutong capsule plus Std reduced the risk of angiographic restenosis by 76% (RR 0.24, 95%CI 0.11~0.45, very low to moderate certainty of evidence), most likely the best intervention. Fufang Danshen dripping pill combined with Std showed superiority over other interventions for relieving recurrence angina, which can reduce the risk by 83% (RR 0.17, 95%CI 0.04~0.51, very low to moderate certainty of evidence) to Std alone. In acute myocardial infarction after PCI, compared with Std, Danhong injection plus Std displayed a significant effect (RR 0.11, 95%CI 0.00~0.69, very low to moderate certainty of evidence) and was the best treatment probably. Chuanxiongqin tablet plus Std was the most effective treatment for reducing target lesion revascularization by 90% (RR 0.10, 95%CI 0.00~0.60, very low to moderate certainty of evidence) compared with Std.Conclusions: The results indicated that CPMs combined with Std reduced the risk of coronary restenosis after PCI. However, the results should be interpreted cautiously due to significant data limitations.